Odpowiedzi

Najlepsza Odpowiedź!
2010-01-08T20:24:22+01:00
Metoda podstawiania;
x=2y+3
-3(2y+3)+3y+3

x=2y+3
-6y-9+3y=3

x=2y+3
-3y-9=3

x=2y+3
-3y=3+9

x=2y+3
-3y=12/;(-3)

x=2y+3
y=-4

x=2razy(-4)+3
y=-4

x=-5
y=-4

przeciwnych współczynników
x-2y=3/razy 3
-3x+3y=3

3x-6y=9
-3x+3y=3

-3y=12/:(-3)
y=-4
3x-6razy (-4)=9
3x+24=9
3x=-15/:3
x=-5

podstawiania;2x+4y=6
-x+y=1

2x+4y=6
y=x+1

2x+4(x+1)=6
y=x+1

2x+4x+4+6
y=x+1

6x=6-4
y=x+1

6x=2/:6
y=x+1

x=dwie szóste
y=x+1

x= jedna trzecia
y=1 i jedna trzecia

przeciwnych współczynników2x+4y=6
-x+y=1/razy2

2x+4y=6
-2x+2y=2

6y=8/:6
y=1 i jedna trzecia

-2x+2razy cztery trzecie=2
-2x+osiem trzecich=2
-2x=2-osiem trzecich
-2x=2-2 i dwie trzecie
-2x=-dwie trzecie/:(-2)
x=jedna trzecia